Time use and spatial influence on transport-related social exclusion, and mental and social health - Dharmowijoyo, D.B.E. (Elsevier Ltd, 2020)
Using a modified three-level modelling method and a multidimensional three-week household time-use and activity diary, this study investigates the interaction of the time duration of individualsâ activities, travel parameters, the built environment and socio-demographics on people's transport-related social inclusion. Such interactions are assumed to affect one's social and mental health on a daily basis, in particular in developing countries where working conditions, time pressures and income and accessibility gaps are much more extreme than in developed countries. The results show that, in developing countries such as Indonesia, even though people believe that they are well integrated within society, have adequate access to various public amenities, have abundant opportunities for varied social participation and more access to various public amenities, many still have mental health problems due to the existence of physical health problems, chronic diseases, the feeling of insecurity resulting from financial burdens and a lack of social security. Having more inclusive transport access, on the other hand, helps people to have better social health. The life stages of individuals, particularly for those who belong to the later stage, correlates with the probability of having mental and social health problems intensified by a worsened financial status and one's need to work for a longer time. Having more predictable activityâtravel patterns and an opportunity for a break from regular work activities during the weekend positively correlates with older people's transport-related social inclusion and positive mental health conditions. More cycling and walking, and the provision of denser public amenities, can contribute to more inclusive transport access and subsequently to one's social and mental health. Moreover, providing a dedicated public transport system for people who reside in Greater Bandung Metropolitan Area is expected to be associated with better transport-related social inclusion and social health. Â© 2020 Hong Kong Society for Transportation Studies